Integrated Digital Portfolio-Based Education Management in LMS: Strategy to Improve Learning Quality and Administration in Educational Units - Syaiful, Rahman; Gunarti Dwi Lestari, Gunarti (Journal of Education Technology and Inovation, 2025)
This study explores the use of social media as a collaborative learning platform in early childhood education (ECE). In the digital era, social media has become increasingly pervasive; however, its potential in facilitating collaboration between educators and parents in the ECE context remains underexplored. This research aims to identify both the opportunities and challenges in implementing social media as a medium for collaborative learning within early childhood education institutions. Employing a qualitative approach, data were collected through participatory observation, in-depth interviews with 12 informants (comprising early childhood educators and parents), and content analysis of selected social media platforms such as WhatsApp, Facebook, and Instagram. Thematic analysis was used to identify key patterns and insights, and data triangulation was applied to ensure the validity and credibility of the findings. The results indicate that social media holds transformative potential to enhance communication, involvement, and co-learning among stakeholders in early childhood education. However, successful implementation requires a systemic strategy that addresses digital literacy, platform appropriateness, and capacity-building for both educators and parents